Elastisitas Permintaan Beras Organik Di Kabupaten Hulu Sungai Utara - Muhammad Zaini; Miranda Romaully Br Sitanggang; Rum Van Royensyah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2019)
This study is aimed to determine the factors that influence the demand of organic rice and its elasticity in Hulu Sungai Utara. This research was conducted in Amuntai City. Data collection was carried out from October 2018 to January 2019. The analysis us is multiple linear regression analysis from the results of calculations using the regression equation Y = 2.564 + 0.002 (X1) + 1.025 (X2) - 0.223 (X3) - 1,511 (X4) + 0.196 (X5) + 0.003 (X6). The results of the analysis for regression obtained F-count 2.672 > F-table 2.53 thus the hypothesis which states that the variable of education level, income, tastes / habits, number of dependents, price of organic rice, and prices of other goods (non-organic rice) have an effect simultaneously to the demand for organic rice. While significantly obtain the results of t test where the value of t-calculation is 2.460 > t-table 1.713. The elasticity of demand for static models is based on price elasticity, the price of organic rice is elastic (7.32 > 1). Based on cross elasticity, the price of other goods (organic rice) is elastic (5.27 > 1). Based on income elasticity, respondents' income is elastic (702,615 > 1).